Studi Komparasi Penggunaan Media Pembelajaran Komik dengan Media Modul Pembelajaran pada Metode Resitasi Pada Hasil Belajar Fisika SMA - Ikah Miftahul Khasanah; Mirza Nurhidayat; Ferawati Ferawati (Universitas Muhammadiyah Purworejo, 2019)
This study aims to determine the differences in student physics learning outcomes using comic learning media with learning module media on the recitation method. This research was conducted at Gunung Putri 2 High School in the second semester of the 2017-2018 school year. The population of this study was taken as many as 60 students from a population of 65 students. The sampling technique used is simple random sampling technique. This study uses a quantitative approach with a quasi-experimental method. The results showed that in the experimental group I obtained normality test Lhitung = 6.062 <7.81 = Ltabel and experimental group II obtained Lhitung = 0.70 <7.81 = Ltable at the significance level α = 0.05 and n = 30, then it can be concluded that the two groups are normally distributed. For the homogeneity test, it was found that Fcount = 1.211 <1.87 Ftable, it can be concluded that the variance between the two groups is the same, meaning that the sample comes from a homogeneous population. Hypothesis testing using t-test obtained by t count = 5.01> t table (α = 0.05; db = 58) = 1.643 and t count = 5.01> t table (α = 0.01; db = 58) = 2.66 , then H0 is rejected. Thus, H0 is rejected which states that there is a difference between student physics learning outcomes using comic learning media with learning module media on the recitation method.